Community Behavioral Knowledge about the Dengue Fever Eradication Program in Sibolahotang Village, SAS, Toba Regency, 2025 - Minaria Minaria; Ricard F Marpaung (Lembaga Pengembangan Kinerja Dosen, 2025)
Dengue Hemorrhagic Fever (DHF) is an acute febrile illness found in tropical regions and caused by four serotypes of viruses from the Flavivirus genus, family Flaviviridae, also known as breakbone fever. DHF has now become an epidemic in more than 100 countries. This disease can be effectively managed through prevention efforts that focus on changing community behavior, including knowledge, attitudes, and actions in responding to the disease. This study aims to describe community behavior regarding the Dengue Fever Eradication Program (PSN) in Toba Regency. The method used in this study was descriptive analytical with a cross-sectional approach. The sample used in this study was 100 randomly selected respondents. Data were collected through a questionnaire designed to explore community knowledge, attitudes, and actions towards the dengue eradication program. Data were then presented in tabular form and analyzed quantitatively. The results showed that community knowledge of the National Dengue Fever Prevention and Eradication Program (PSN) was quite good, with a score of 90.14%. However, knowledge about dengue fever itself varies, with nearly half of respondents reporting poor knowledge. Public attitudes toward dengue fever eradication efforts were very positive, with 100% of respondents expressing support for dengue eradication efforts. Public support for dengue fever eradication efforts was also generally positive, with a score of 87.25%. The study concluded that public attitudes toward dengue fever eradication efforts in Toba Regency were generally positive. However, there are still gaps in public knowledge about dengue fever that need to be addressed through further education. This study provides important insights for the government and relevant parties to improve the effectiveness of dengue eradication programs in the region.